2013
DOI: 10.1166/acl.2013.1007
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Structural Properties of PVA Capped Gold Nanoparticles and Their Antibacterial Efficacy

Abstract: Gold nanoparticles (AuNPs) were prepared by UV-irradiation technique at different irradiation times. Polyvinyl alcohol with two different molecular weights was used as encapsulating agent. The PVA capped gold nanoparticles showed surface plasmon bands at 531 nm after 1 h UV-irradiation and emission band at 365 nm and 394 nm with an excitation wavelength 300 nm. TEM micrograph showed that majority of the AuNPs are spherical, some are hexagonal, triangular and rod shaped. The XRD study clearly indicates formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Based on these two kinds of chemical bonds, many stable structures like “egg box” were formed by SA chains [ 23 ]. In the next step, PVA chains were physically crosslinked with SA-AuNPs due to the coordination interaction between sodium alginate-capped AuNPs and hydroxyl groups of PVA [ 30 ]. Then the hydrogel matrix dispersion prepared was cast on the bottom of glass beakers and allowed the solvent to evaporate and dry until the formation of the membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these two kinds of chemical bonds, many stable structures like “egg box” were formed by SA chains [ 23 ]. In the next step, PVA chains were physically crosslinked with SA-AuNPs due to the coordination interaction between sodium alginate-capped AuNPs and hydroxyl groups of PVA [ 30 ]. Then the hydrogel matrix dispersion prepared was cast on the bottom of glass beakers and allowed the solvent to evaporate and dry until the formation of the membranes.…”
Section: Resultsmentioning
confidence: 99%
“…They were analyzed through FE-TEM ( Figure S2 ). The AuNPs used in the LSPR sensor chip had a generally uniform size of 12.32 ± 1.01 nm ( Figure S2a ) with a lattice spacing of 0.23 nm, which was matched with the (111) crystal plane, indicating that the synthesized AuNPs were suitable ( Figure S2b ) [ 33 ]. The LSPR chip’s size measurements were precisely maintained according to the size of the UV cuvette cell to fabricate a highly stable and robust cuvette-type LSPR sensor for easy handling while testing with a UV–Vis spectrophotometer.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were found for hybrid Tyrosine-capped Ag-H 3 PW 12 O 40 and Ag-H 3 PMo 12 O 40 NP systems, in which neither of the two pristine POMs exhibited antibacterial activity when tested alone. [57] Neither this corecoating synergistic effect nor any observation of bacteria inhibition is present when Au NPs are coated and stabilized with non-active capping ligands like citrate, [53] PVA, [58] or PEG [59] (polyethylene glycol). However, we have recently shown that Au III solutions are able to induce bacterial wall damage, being much more harmful against Gram-negative than Gram-positive bacteria.…”
Section: Bactericidal Activity Of Au@pom Nanoparticlesmentioning
confidence: 99%